CONTEST CORNER: The 2020 State Tournament of Mathematics Results - Flick, Michael; Kuchey, Debora (Ohio Journal of School Mathematics, 2020)
In this article, the authors summarize results from the 2020 State Tournament of Mathematics. Included with the results and statistics are sample problems from the contest.